2017
DOI: 10.1111/ane.12798
|View full text |Cite
|
Sign up to set email alerts
|

Wearables in epilepsy and Parkinson's disease—A focus group study

Abstract: Patients need to feel well informed and find an added value in using wearables. Wearables need to be user-friendly, have an attractive design, and show clinical efficacy in improving disease management. Variations in perceptions regarding integrity, benefits, and effectiveness of monitoring indicate possible conflicts of expectations among participants. The engagement of end users, patients, and health professionals, in the design and implementation process, is crucial for the development of wearable devices t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
81
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 20 publications
12
81
3
Order By: Relevance
“…Adaptation Challenge 2 -Compliance: Participants in prior studies reported difficulty in using and charging the device regularly. It is difficult for a patient to charge the device, since it may involve taking the device off and wearing it on again [13]. Larger and bulky batteries help in increasing the lifetime of the device, but they also make the device uncomfortable to wear.…”
Section: Wearable Health: Challenges and Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptation Challenge 2 -Compliance: Participants in prior studies reported difficulty in using and charging the device regularly. It is difficult for a patient to charge the device, since it may involve taking the device off and wearing it on again [13]. Larger and bulky batteries help in increasing the lifetime of the device, but they also make the device uncomfortable to wear.…”
Section: Wearable Health: Challenges and Solutionsmentioning
confidence: 99%
“…However, clinical visits, which are typically weeks apart, capture only a snapshot of the symptoms [6]. This introduces complications in therapy decisions, since symptoms vary over time, and patients' recall accuracy is not reliable [13]. Moreover, access to highly trained specialists can be challenging in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With an attractive integrated design, they may fulfil the need of patients with epilepsy to have a better outpatient disease management, while avoiding social stigmatization [6]. Several commercially available devices with proprietary algorithms have been proposed to be effective for TCSs detection, including a wrist watch with built-in accelerometers [7], accelerometry sensors combined with audio recordings [8], or other modalities, such as electrodermal activity [9,10] and heart rate [11].…”
Section: Introductionmentioning
confidence: 99%